Invisible to Radar: Contributions of International Law to Combat Invasive Species in Mexico and Tamaulipas - Herrera-Izaguirre, Juan Antonio (Universidad Autónoma de Tamaulipas, 2010)
In the last decades has been remarkable progress in international law to assist in the conservation of the environment. Several international agreements have been signed by Mexico to stem the Invasive Species Challenge. This article analyzes the effectiveness of two international agreements